2020
DOI: 10.1101/2020.05.04.070177
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanistic insights into RNA binding and RNA-regulated RIG-I ubiquitination by TRIM25

Abstract: TRIM25 is a ubiquitin E3 ligase active in innate immunity and cell fate decisions. Mounting evidence suggests that TRIM25’s E3 ligase activity is regulated by RNAs. However, while mutations affecting RNA-binding have been described, the precise RNA binding site has not been identified nor which domains are involved. Here, we present biophysical evidence for the presence of RNA binding sites on both TRIM25 PRY/SPRY and coiled-coil domains, and map the binding site on the PRY/SPRY with residue resolution. Cooper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 94 publications
1
6
0
Order By: Relevance
“…As opposed to TXN, scFPR1, and SNTB1, NMR resonances of TRIM25 exhibited clear CSPs upon addition of five molar equivalents of poly(U) 15-mer RNA, confirming its ability to bind single-stranded RNA (Figure 1D). Follow-up NMR studies and detailed biophysical characterization of the RNA binding of TRIM25 has been published in the meantime (Haubrich et al, 2020), where we could confirm that TRIM25 has a preference for stem loop RNA and binds single-stranded as well as structured RNA on two different binding sites on the PRYSPRY domain. Additionally, we could also confirm that the coiled-coil binds to RNA synergistically with the PRY/SPRY domain.…”
Section: Resultssupporting
confidence: 56%
See 3 more Smart Citations
“…As opposed to TXN, scFPR1, and SNTB1, NMR resonances of TRIM25 exhibited clear CSPs upon addition of five molar equivalents of poly(U) 15-mer RNA, confirming its ability to bind single-stranded RNA (Figure 1D). Follow-up NMR studies and detailed biophysical characterization of the RNA binding of TRIM25 has been published in the meantime (Haubrich et al, 2020), where we could confirm that TRIM25 has a preference for stem loop RNA and binds single-stranded as well as structured RNA on two different binding sites on the PRYSPRY domain. Additionally, we could also confirm that the coiled-coil binds to RNA synergistically with the PRY/SPRY domain.…”
Section: Resultssupporting
confidence: 56%
“…Additionally, we could also confirm that the coiled-coil binds to RNA synergistically with the PRY/SPRY domain. TRIM25 binding by RNA has an effect on RIG-I ubiquitination and the interferon response, suggesting an involvement of RNA in the host defense against viral infection (Haubrich et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Structural analysis highlighted that TRIM25 RING domain dimerization leads to higher-order oligomerization and catalytic activation of TRIM25, which is required for RIG-I ubiquitination and subsequent activation [ 35 ]. Recent studies have shown that TRIM25 also possesses RNA-binding activity, via its PRY/SPRY domain and coiled-coil domain (CCD), which regulates the ubiquitin E3 ligase activity of TRIM25, its oligomeric state, localization within the cell, and antiviral activity [ 36 , 37 , 38 ]. Several viruses have evolved to antagonize the TRIM25-RIG-I signaling axis, thereby limiting IFN responses ( Figure 1 ).…”
Section: Viral Evasion Of Ubiquitin-mediated Rlr Responsesmentioning
confidence: 99%